The Implementation of Character Education In The SPK (Joint-Educational Unit) Kindergarten - Sabdaningdyah, Lidia -; Made Sudana, I; Kuswardinah, Asih (Educational Management, 2021)
Education has crucial roles for early childhood children to prepare them with a strong basic foundation for further education. It is important to develop human resources that are not only eligible academically. The Bina Bangsa Kindergarten adopts a curriculum from other countries. It also includes the character education curriculum. As a Joint Educational Unit, the school has different approaches. It accommodates not only domestic learners and teachers but from many countries and cultures. This qualitative research collected the data comprehensively and accurately. The subjects were the principal, home teachers, and parents. The findings were from various methods, such as interviews, documentation study, and interviews. They showed that the character education implementation had been structured into lessons and integrated into all school activities. The findings also showed that the learning activities and cooperation with the learners' parents were already excellent by applying a multicultural approach. The character education was already excellent by the supervision of both the principal and the parents. Various social and religious activities supported character education. They involved cooperation from the parents to practice the character values at home.